2017
DOI: 10.18632/oncotarget.17692
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 induces vitamin D receptor and HDAC11 binding to relieve the promoter of the tight junction proteins

Abstract: Intestinal epithelial barrier dysfunction and vitamin D (VitD)-deficiency play a critical role in a large number of diseases. The histone deacetylases (HDAC) are associated with a large number of immune diseases. This study tests a hypothesis that the interaction between VitD and HDAC is associated with the regulation of epithelial barrier functions. In this study, human intestinal epithelial cell line, T84 cells, was cultured into monolayers to be used as a model to test the epithelial barrier functions. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…These results suggested that claudins have different biology function in the different cells or tissues. In our study, other TJ molecules such as ZO-1 and occludin were significantly reduced in VDR -/mice, suggesting that chronic inflammation induced by VDR deletion may affect the barrier function of TJs and may correlate with the interaction between VDR and histone deacetylase 11 (HDAC11) 39 .…”
Section: Claudin-10mentioning
confidence: 50%
“…These results suggested that claudins have different biology function in the different cells or tissues. In our study, other TJ molecules such as ZO-1 and occludin were significantly reduced in VDR -/mice, suggesting that chronic inflammation induced by VDR deletion may affect the barrier function of TJs and may correlate with the interaction between VDR and histone deacetylase 11 (HDAC11) 39 .…”
Section: Claudin-10mentioning
confidence: 50%
“…Although there is a variety of functions and routes that vitamin D/VDR plays a role, there are few studies exploring gene regulation of junctional proteins [ 117 ]. Liu et al showed that VDR binds to histone inhibiting transcription of ZO-1, claudin-5, and occludin genes [ 118 ]. Zhang et al have identified that VDR increases the tight junction protein claudin-2 as a direct target of the VDR signaling pathway [ 62 ].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…103 Curcumin is taken up by the intestinal epithelial cells 104 and Bartik et al showed that curcumin binds to intracellular vitamin D receptor in intestinal epithelial cells and facilitates colon cancer chemoprevention. 105 It needs to be emphasized that interaction between vitamin D and HDAC is associated with the regulation of epithelial barrier functions 106 and it is likely that by enhancing vitamin D signaling, curcumin regulates barrier function.…”
Section: Other Intestine-specific Effects Of Curcuminmentioning
confidence: 99%